PIGGYBACK TAX: POTENTIAL FOR TAX EXTENSIFICATION THROUGH THE IMPOSITION OF MOTOR VEHICLE TAX (PKB) OPTIONS IN THE PROVINCE OF EAST NUSA TENGGARA (NTT) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
Objective: This study aims to analyze the potential implementation of an additional motor vehicle tax (PKB) based on Law Number 1 of 2022 concerning Central and Regional Financial Relations (HKPD Law) to increase regional original revenue (PAD) for the East Nusa Tenggara (NTT) Provincial Government and Kupang City. Method: A quantitative approach was used using time-series simulations (2021–2023) and trend forecasting (2024–2029) using Microsoft Excel. Data on PKB realization, vehicle numbers, and tax rates were analyzed to model revenue under both a revenue-sharing framework (Law No. 28/2009) and an additional 66% tax burden. Results: The OPsen system significantly increased district/city regional revenue compared to the revenue-sharing system. In 2023, the OPsen contributed 39.76% (Rp 116.17 billion) to Kupang City's Regional Original Revenue (PAD), compared to 10.15% (Rp 29.67 billion) under the revenue-sharing framework. This aligns with the objectives of fiscal decentralization, namely strengthening regional tax authority while maintaining administrative efficiency. However, horizontal disparities may arise due to variations in the number of registered vehicles across regions. Implications: The OPsen mechanism enhances fiscal autonomy but requires strong public outreach to mitigate potential demand shocks from higher tax burdens. Local governments should diversify revenue streams, such as optimizing levies related to tourism and village-owned enterprises (BUMDes), to reduce overreliance on the Motor Vehicle Tax (PKB). Policymakers must balance fairness and efficiency in implementing additional levies to ensure sustainable regional fiscal health.
Keywords: Fiscal decentralization; motor vehicle tax (PKB); additional levies (Opsen); local revenue (PAD); tax simulation